Pettis Integrability in L1E′ [E] Related to the Truncation (European Journal of Pure and Applied Mathematics, 2022)
We study the Pettis integrability in terms of truncation. We focus our study particularly on space L1E′ [E].
Keywords: Convergence, dual space, Gelfand integral, Pettis integral, The space $L^{1}_{E'}\left[E\right]$, Truncation.